2022
DOI: 10.55433/gsbd.110
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Covid-19 Pandemia Process on Anxiety and Self-Confidence Levels in Clinical Deci̇si̇on Maki̇ng in Last Class Nursing Students

Abstract: To investigate the effect of the COVID-19 pandemic process on anxiety and self-confidence levels in clinical decision making in last class nursing students. The sampling of this descrıptıon study consisted of 161 last class nursıng students. The data were collected using the "Personal Information Form and Clinical Decision Making Anxietyand Self-Confidence Scale in Nursing". Anxiety total score of last class nursing students in clinical decision making was 73.03 ± 24.66 (27.00- 162.00) and total self-confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In a study by Arda Sürücü et al using the same scale, it was reported that the student's total anxiety score in clinical decision-making was 73.03 ± 24.66. It was stated that nursing students' anxiety increased in clinical decision-making during the pandemic (12). Another study on nursing students during the pandemic showed that their anxiety levels rose with the pandemic situation (16).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study by Arda Sürücü et al using the same scale, it was reported that the student's total anxiety score in clinical decision-making was 73.03 ± 24.66. It was stated that nursing students' anxiety increased in clinical decision-making during the pandemic (12). Another study on nursing students during the pandemic showed that their anxiety levels rose with the pandemic situation (16).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety may result from interrupting students' education and transition to online learning, inadequate distance learning strategies, and increased homework and workload. Moreover, the most significant sources of anxiety are thought to be related to the fear of infection and transmission regarding themselves and their loved ones brought by continuing clinical practice, lack of personal protective equipment, and practices required by COVID-19 precautions in clinics (9,12,16,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations